Making your first feature film : lessons I learned the hard way - Bagnato, Dominick (McFarland & company, 2017)
"Chronicling the making of his debut feature film, the author describes the practical steps needed take a project from early concept to the first day of photography--details most filmmaking guides don't include. A scene-by-scene breakdown describes the lessons learned during the production and postproduction phases. Options for what to do after completion are also covered"--